2006
DOI: 10.1002/chem.200500999
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene as Chromophore and Electrophore: Encapsulation in a Rigid Polyphenylene Shell

Abstract: Starting from the fourfold ethynyl-substituted chromophore 1,3,6,8-tetraethynylpyrene as core, a series of polyphenylene dendrimers was prepared in high yield by combining divergent and convergent growth methods. The fluorescence quantum yields (Q(f)>0.92) of the encapsulated pyrene chromophore were independent of the size of the polyphenylene shell. Fluorescence quenching studies and temperature-dependent fluorescence spectroscopy were performed to investigate the site isolation of the core. They indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 58 publications
4
91
0
Order By: Relevance
“…The band with a maximum at 319 nm can be assigned to the absorption of PBD [38], similar to that of PYPBD (a pyrene-cored polyphenylene dendrimer with PBDs in the periphery, see Scheme S1). The other band (λ max : 392 nm, ε:~50,000 L·mol −1 ·cm −1 ) is much sharper and originates from π-π* transitions of the pyrene core [24,40,41]. Both dendrimers are readily soluble (≥8 g/L) in organic solvents, e.g., DCM, THF and toluene.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The band with a maximum at 319 nm can be assigned to the absorption of PBD [38], similar to that of PYPBD (a pyrene-cored polyphenylene dendrimer with PBDs in the periphery, see Scheme S1). The other band (λ max : 392 nm, ε:~50,000 L·mol −1 ·cm −1 ) is much sharper and originates from π-π* transitions of the pyrene core [24,40,41]. Both dendrimers are readily soluble (≥8 g/L) in organic solvents, e.g., DCM, THF and toluene.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…The band with a maximum at 319 nm can be assigned to the absorption of PBD [38], similar to that of PYPBD (a pyrene-cored polyphenylene dendrimer with PBDs in the periphery, see Scheme S1). The other band (λmax: 392 nm, ε: ~50000 L·mol −1 ·cm −1 ) is much sharper and originates from π-π* transitions of the pyrene core [24,40,41]. The photoluminescence spectra (PL) of these dendrimers showed that the emission of the donoracceptor dendrimers, PYCAB and PYPBD were all identical (λmax: ~431 nm and a weak shoulder: ~455 nm) both for excitation of the surface and the core groups (Figure 2), revealing that the emission of the donor-acceptor dendrimers can be attributed to an efficient surface-to-core energy transfer [24,40,41].…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations